PHYSICOCHEMICAL CHARACTERIZATION OF BIODEGRADABLE PLASTIC FROM UWI TUBER STARCH (DIOSCOREA ALATA) WITH SORBITOL AND CMC (CARBOXYMETHYL CELLULOSE) AS PLASTICIZER ADDITION - Dina Wahyu Indriani; Sumardi Hadi Sumarlan; Siti Munawaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2019)
Uwi tubers (Dioscorea alata) are widely used as biodegradable plastics materials because it contains high starch content about 75,6 – 84,3%. Biodegradable plastics can be used as a decent food wrapping. The purpose of this research is to study the process of making biodegradable plastics and analyze the effect of a adding CMC (carboxymethyl cellulose) and sorbitol plasticizers on the physicochemical properties of biodegradable plastics from uwi tuber starch with various parameters, solubility, thickness, tensile strength, elongation, modulus Young, compressive strength, biodegradability and surface morphology of functional groups. The making of plastic biodegradables is based on the melt intercalation method. Uwi tuber starch composition used was 5 grams, the combination of CMC concentration used was 0 gram; 0,20 gram; 0,30 gram; 0,40 gram. While the variations in the volume of sorbitol used are 2 ml, 3 ml, 4 ml, 5 ml. The results of this study indicate that the additon of 0 gram CMC and 2 ml of sorbitol produce tensile strength values of 7,66 MPa, the best modulus Young is 5,52 MPa. The compressive strength values is lower that is equal to 0,150 kgf, the best elongation value is at the addition of CMC 0,20 gram and sorbitol 5 ml that is equal to 39,44%. The concentration of the CMC addition and sorbitol plasticizer on biodegradable plastic affects physical properties in SEM testing with the additon of 0 gram CMC and sorbitol 2 ml, which results are denser when compared with the addition of 0,40 gram CMC and 5ml sorbitol. In the FTIR test, there are C-O alcohol/ester/carboxylic acid/eter functional groups in waves 1050-1300. Plastics with the highest concentrations of CMC and sorbitol need 7 days to be degraded.